An international survey on the awareness, use, preference, and health perception of novel psychoactive substances (NPS). (8th May 2017) - Deligianni, Elena; Corkery, John M.; Schifano, Fabrizio; Lione, Lisa A.
Abstract: Objective: This survey investigated the level of public awareness, preference, and motivation of novel psychoactive substances (NPS) use as well as knowledge of potential associated health risks. Methods: A Bristol Online Survey was advertised through social media and a drug forum "Bluelight" between January 7 and February 7, 2015. Results: Responses were received from 17 countries, mainly from Europe. Most responses (83%) came from university educated students. Two‐thirds (65%) of the 168 respondents were aware of NPS. Awareness was significantly increased in those with bisexual or homosexual orientation ( p  < .05) and those in employment ( p  < .05). Fourteen percent of the 168 respondents were users of NPS, and use was significantly affected by age and employment ( p  < .01) but unaffected by level of education ( p  > .05). Nearly half of the NPS users perceived NPS to carry either a low risk to health (20%) or did not know whether or not they posed a health risk (29%). Conclusions: These survey data indicate that awareness of NPS and, importantly, perception of the potential health risks associated with NPS use is lacking. NPS awareness and use is higher in those in employment but is unaffected by level of education. This highlights the need for targeted drugs education intervention by policy‐makers in schools and universities.